2015
DOI: 10.1517/14656566.2015.1058780
|View full text |Cite
|
Sign up to set email alerts
|

Lurasidone in the treatment of schizophrenia: a critical evaluation

Abstract: Lurasidone is a benzoisothiazole with potent dopamine D2 and serotonin 5HT2A antagonist and serotonin 5HT1A partial agonist properties (like other second-generation antipsychotic agents) with additional potent 5HT7 and alpha2C noradrenergic antagonism. It has little or no activity at the alpha1 and alpha2A noradrenergic, 5HT2C serotonergic, histaminergic and cholinergic receptors. Available only in an oral formulation, it is effective in once-daily dosing (40 - 160 mg/day) and its absorption is affected by foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…Clinical trials show that antipsychotic medications significantly improve psychotic symptoms for patients with schizophrenia [ 221 , 222 , 223 ]. Atypical antipsychotics may partially normalize ROS metabolism and oxidative stress [ 75 ].…”
Section: Role Of Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials show that antipsychotic medications significantly improve psychotic symptoms for patients with schizophrenia [ 221 , 222 , 223 ]. Atypical antipsychotics may partially normalize ROS metabolism and oxidative stress [ 75 ].…”
Section: Role Of Antipsychoticsmentioning
confidence: 99%
“…Lurasidone is an atypical antipsychotic with high affinity for dopamine D2 receptors, noradrenaline alpha-2C receptors, and serotonin 5-HT2A, 5-HT1A, and 5HT7 receptors [ 222 , 250 , 251 ]. A study of 2373 patients with acute schizophrenia found lurasidone was safe and effective, especially with a daily dose of 80 mg [ 251 ].…”
Section: Role Of Antipsychoticsmentioning
confidence: 99%
“…Lurasidone’s approval as a treatment for schizophrenia was based on the results of a clinical development programme that included five similarly designed, 6-week-long, fixed-dose, placebo-controlled trials and several long-term, open-label maintenance studies (see Electronic Supplementary Material [ESM] Table S1 for details) [1927]. Details of these clinical trials have been extensively published and reviewed elsewhere [28, 29]; therefore, only a brief overview of key data is provided here.…”
Section: Clinical Trials Of Lurasidone In Adults With Schizophreniamentioning
confidence: 99%
“…Lurasidone, a second-generation atypical antipsychotic slowly metabolizing medication, has been proven to be successful in treating both disorders [ 1 , 2 ]. Recent literature demonstrated outstanding safety and favorable metabolic adverse effect profiles, making it a compelling option in treating schizophrenia and bipolar disorder [ 3 ]. Lurasidone treatment is associated with significantly less weight gain when compared to olanzapine and quetiapine [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%